Posterior Dislocation Of The Hip Joint Due To Trauma In Children: A Three-Case Series - Uzair Rashid, Zia ur Rehman, Sarmad Khalil, Hizbullah Riaz Ansari, Muhammad Ali Ayub, Omar Aziz, Ashfaq Jadoon. Amer Aziz (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To appraise cases that presented with posterior dislocation of the hip secondary to trauma in paediatric age group and to analyse difficulties along with challenges that arise in the diagnosis (both radiological and clinical), treatment plan, complications and the outcome of such injury in children. Methods: Three children with traumatic posterior hip dislocation and a mean age of 3.3±0.47 years who were followed-up at 6 months were assessed. Results: The primary early treatment was closed reduction, executed within six hours of injury. The three subjects were treated with reduction under anaesthesia. The adjuvant treatment was immobilization via hip spica. Follow up was uneventful. Conclusion: Dislocation of the hip joint due to trauma should be attended to as early as possible with emphasis on achieving anatomical reduction preferably via reduction and close follow up.